In a silent way [videorecording (DVD)] - Dorian, Nicholai; Tuttle, Nicholas; Slajer, Vratislav; Levin, Collin; Dorian, Nicolai; Meskimen, Jim; Stucky, Dillon (Filmhub, 2025)
A dark comedy about a young jazz musician who hires his best friend Dylan to follow his every move as he attempts to become a jazz legend.